تأثير التسميد البوتاسي في إنتاجية الصويا وفي التركيب الكيميائي للأوراق والبذور - عبد العزيز محمد; محمد يوسف (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2002-2003 لدراسة تأثير البوتاسيوم على تركيز العصير الخلوي والتركيب الكيميائي لأوراق الصويا وبذورها، استخدم لذلك 5 معدلات هي 0، 30، 60، 90، 120 كغ K2O/هـ بينت الدراسة مايلي: أدى استخدام معدلات متزايدة من K2O إلى زيادة معنوية في تركيز العصير الخلوي في الأوراق في مرحلة الإزهار، ومرحلة تشكل القرون، ومرحلة النضج،وفي زيادة محتواها من الآزوت والفوسفور والبوتاس مقارنة مع الشاهد بينما لم تكن الفروق معنوية بين المعاملات المسمدة في محتوى الآزوت والفوسفور، كما أثبتت الدراسة زيادة معنوية في محتوى البذور من الزيت والبروتين مقارنة مع الشاهد، بالمقابل انخفضت نسبة الرطوبة في البذور مع زيادة معدلات البوتاسيوم. The research was carried out during 2002-2003 to study the effect of potassium fertilizer on cell juice concentration and chemical content of leaves and seeds of soybean, using 5 rates these 0, 30, 60, 90 and 130 Kg K2O/ha1. The results revealed that using increasing rates of K2O significantly increased cell juice concentration in leaves at flowering stage, pods formation stage and maturity stage. It also increased continent of N, P, K compared with he control. However, there were not significant increases of content N. P. between the treatments potassium fertilization. The study showed significant increases in the contents of oil and protein seeds compared with the control, on other side decreased of the seeds moisture percentage increases the rates potassium fertilizer.